A phase I/II trial of WT1-specific TCR gene therapy for patients with acute myeloid leukemia and active disease post-allogeneic hematopoietic cell transplantation: skewing towards NK-like phenotype impairs T cell function and persistence - Francesco Mazziotta; Lauren E. Martin; Daniel N. Egan; Merav Bar; Sinéad Kinsella; Kelly G. Paulson; Valentin Voillet; Miranda C. Lahman; Daniel Hunter; Thomas M. Schmitt; Natalie Duerkopp; Cecilia C. S. Yeung; et al. (Nature Communications)
Abstract Relapsed and/or refractory acute myeloid leukemia (AML) post-allogeneic hematopoietic cell transplantation (HCT) is usually fatal. We previously reported that post-HCT immunotherapy with Epstein-Barr virus (EBV)-specific donor CD8+ T cells engineered to express a Wilms Tumor Antigen 1-specific T-cell receptor (TTCR-C4) appeared to prevent relapse in high-risk patients. In this phase I/II clinical trial (NCT01640301), we evaluated safety (primary endpoint), persistence and efficacy (secondary endpoints) of EBV- or Cytomegalovirus (CMV)-specific TTCR-C4 in fifteen patients with active AML post-HCT. Infusions were well tolerated, with no dose-limiting toxicities or serious adverse events related to the product. However, TTCR-C4 cells did not clearly improve outcomes despite EBV-specific TTCR-C4 cells showing enhanced potential for prolonged persistence compared to CMV-specific TTCR-C4. Investigating the fate of persisting TTCR-C4, we identified a shift towards natural killer-like (NKL) terminal differentiation, distinct from solid tumor-associated canonical exhaustion programs. In one patient, treatment with azacitidine appeared to mitigate this NKL skewing, promoting TTCR-C4 persistence. These findings suggest that AML drives a distinct form of T-cell dysfunction, highlight the need for targeted approaches that preserve T-cell fitness, ultimately improving the efficacy of cellular therapies for AML.